Valuing specialised property using the DCF profits method. Issue 6 (5th September 2016) - Jansen van Vuuren, David
Abstract : Purpose: The purpose of this paper is twofold: primary, to argue that the profits method, specifically a discounted cash flow (DCF)-based profits method, should be the preferred method of valuation when valuing specialised property. Secondary, to make technical recommendations in the application of the method. Design/methodology/approach: Literature was reviewed on the theory of the profits method as well as physical valuations performed in practice. Improvements for the profits method are suggested from the review of six valuations conducted in South Africa in the specialised property sectors. A qualitative approach is followed in the research as broad principles are extracted from the valuation reports as implications and improvements for the profits method. Findings: The profits method is more flexible and sophisticated than the cost approach in taking into account systematic and unsystematic risk. The profits method is more accurate than the cost approach in delivering a true reflection of the value of specialised property for any purpose but specifically for mortgage lending purposes and reduces the credit exposure risk of financial institutions. It also decreases pricing inefficiencies to be exploited by buyers and sellers. Practical implications: Three improvements to the profits method are suggested. First, revenue could be forecasted based on a probability-weighted approach. Second, a modified capitalisation rate is suggested to the capitalisation rate formula in the calculation of G. Third, a market rental aggregation anchoring and judgement-based approach is suggested as rationale for determining the hypothetical rental split. Originality/value: There seems to be a general lack in literature on the profits method of valuation and its application to specialised properties, specifically a DCF-based approach, with this paper being a technical contribution to the body of knowledge on this topic.